THE EFFECT OF ONLINE LEARNING ENGLISH AT SENIOR HIGH SCHOOL - Rara, Daun; Muhammad Yahrif; Hasnani (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MEGAREZKY, 2022)
The aim of this study was to find out The Effect of Online Learning English at SMA NEGERI 12 MAKASSAR that consisted of 35 students. This research was ex post facto quantitative research which was implemented in four stages which was observation, interview, documentation and analysis data, the collecting data method used quantitative data. Interview was the main data while observation and documentation was the supporting data. The result of the data shows that the variable X has no significant effect on the variable Y. From the results testing the hypothesis proved that